(untitled) (Bangladesh Journal of Microbiology, 2016)
Different types of ice creams available in Dhaka were analyzed for their bacteriological quality. A total number of 24 ice cream samples from two different brands (Brand 1 and 2) were collected from street vendors and local shops of different parts of Dhaka city. Average total viable count in the Brand 1 samples ranged from 9.5x102 to 4.72 x104 cfu/ml, while total coliform count and fecal coliform counts were 2.3x101 to 2.43x103 cfu/ml and zero to 100 cfu/ml, respectively. In case of Brand 2, average total viable count, total coliform count and fecal coliform count were 9.5x103 to 4.43x104 cfu/ml; 10 to 2.49x103 cfu/ml and zero to 200 cfu/ml, respectively. Bacteria isolated from the ice cream samples included Staphylococcus sp. (96%), Bacillus sp (50%), Listeria sp. (41.66%), Micrococcus sp. (12.5%), Escherichia coli (8.33%) and Klebsiella sp (8.33%). Presence of these bacteria in the ice cream indicates the lack of good manufacturing practice in the production of ice cream, which imposes great risk to the consumers. Bangladesh J Microbiol, Volume 29, Number 1, June 2012, pp 41-43